A survey of East Palaearctic Gnaphosidae (Araneae). 8. New data on Berlandina and Gnaphosa from Mongolia - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2017)
Two new species: Berlandina litvinovi sp. n. and Gnaphosa zonsteini sp. n. are described based on both sexes from Western Mongolia. The females of Berlandina koponeni Marusik, Fomichev & Omelko, 2014 and Berlandina nakonechnyi Marusik, Fomichev & Omelko, 2014 are described for the first time. Gnaphosa ustyuzhanini Fomichev, Marusik & Omelko, 2013, known from males, is synonymized with Gnaphosa rasnitsyni Marusik, 1993, known from females. Berlandina koponeni is recorded from China for the first time. Descriptions, illustrations and a map of distribution records are provided.